The Effect Of Internal Communication, Work Environment And Job Description On Employee Performance. (Study at PT Sinar Surya Alumindo) - Layarda Tarihoran; Ibnu Haris Nasution (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2023)
The purpose of this study was to determine and analyze the influence of internal communication, work environment and job descriptions on employee performance at PT Sinar Surya Alumindo. The population in this study were all employees of PT Sinar Surya Alumindo, a total of 65 people and the sample set was 65 people using a saturated sample. Data collection techniques in this study used questionnaires and observation. Data analysis techniques in this study used multiple linear regression tests, classical assumption tests, hypothesis tests (t-test and F-test), and the coefficient of determination. Data processing in this study uses SPSS Version 26. Partially, internal communication has a significant influence on employee performance. Partially, internal communication, work environment and job descriptions have a significant influence on employee performance. Partially and simultaneously internal communication, work environment and job descriptions have a significant influence on employee performance at PT Sinar Surya Alumindo